2015
DOI: 10.1038/ncomms7685
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear translocation of ERK1/2 as an anticancer target

Abstract: A hallmark of the ERK1/2 functioning is their nuclear translocation, which is mainly required for the induction of proliferation. Activated ERK1/2 molecules that remain in the cytoplasm initiate other activities, including immediate feedback loops. Prevention of the nuclear translocation should therefore inhibit proliferation, without affecting cytoplasm-induced cellular processes. Here we present an NTS-derived myristoylated phosphomimetic peptide, which blocks the interaction of importin7 and ERK1/2, and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 37 publications
4
119
1
2
Order By: Relevance
“…ERK1/2 is activated through phosphorylation of activation-loop residues threonine (Thr) 202/tyrosine (Tyr) 204 and Thr 185/Tyr 187, respectively. Activated ERK1/2 translocates into nucleus and participates in the regulation of G1- to S-phase transition, and the nuclear translocation of ERK1/2 is served as an anticancer target [25, 26]. So, we want to clarify whether ERK-pathway was activated in G1/S-phase arrest induced by Ary.…”
Section: Resultsmentioning
confidence: 99%
“…ERK1/2 is activated through phosphorylation of activation-loop residues threonine (Thr) 202/tyrosine (Tyr) 204 and Thr 185/Tyr 187, respectively. Activated ERK1/2 translocates into nucleus and participates in the regulation of G1- to S-phase transition, and the nuclear translocation of ERK1/2 is served as an anticancer target [25, 26]. So, we want to clarify whether ERK-pathway was activated in G1/S-phase arrest induced by Ary.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, nonresponsive tissue was associated with cytoplasmic ERK [79] . Further, the nuclear import protein importin7 facilitates ERK nuclear translocation by recognition of the phosphorylated nuclear translocation signal (NTS), and an NTS-derived phosphomimetic peptide that blocks nuclear translocation of ERK impairs the growth of RAS - or BRAF -mutant tumor cell lines [80] . Because many nuclear ERK substrates are associated with cell proliferation, whereas ERK negative feedback targets are cytosolic (Figure 5), the selective inhibition of phosphorylation of ERK nuclear substrates might favor inhibition of tumor growth.…”
Section: Erk Substratesmentioning
confidence: 99%
“…This combination provides a possible treatment for this disease, which currently does not have an effective treatment. We also showed that the EPE peptide effectively inhibits tumour growth in xenograft models of Ras and B-Raf-transformed cancers, and most importantly, we showed that this inhibitor is less vulnerable to development of resistance than the clinically used B-Raf inhibitor vemurafenib [126]. …”
Section: Inhibiting the Nuclear Translocation Of Mapks As A Tool To Cmentioning
confidence: 99%
“…Recently, our group undertook to prevent ERK1/2 nuclear translocation by preventing the interaction of ERK1/2 with its nuclear shuttling carrier importin7. We synthesized a myristoylated phosphomimetic peptide (EPE peptide) based on the interaction site of ERK1/2 with importin7 (NTS; [126]). This peptide was predicted to bind to importin7 and compete with the interaction of ERK1/2 with importin7, and consequently abolish the nuclear translocation of ERK1/2.…”
Section: Inhibiting the Nuclear Translocation Of Mapks As A Tool To Cmentioning
confidence: 99%